THE MARTIAN ATMOSPHERIC BOUNDARY LAYER - Petrosyan, A; Galperin, B; Larsen, SE; Lewis, SR; Maeaettaenen, A; Read, P; Renno, N; Rogberg, L; Savijarvi, H; Siili, T; Spiga, A; Toigo, A; et al. (2011)
The planetary boundary layer (PBL) represents the part of the atmosphere that is strongly influenced by the presence of the underlying surface and mediates the key interactions between the atmosphere and the surface. On Mars, this represents the lowest 10 km of the atmosphere during the daytime. This portion of the atmosphere is extremely important, both scientifically and operationally, because it is the region within which surface lander spacecraft must operate and also determines exchanges of heat, momentum, dust, water, and other tracers between surface and subsurface reservoirs and the free atmosphere. To date, this region of the atmosphere has been studied directly, by instrumented lander spacecraft, and from orbital remote sensing, though not to the extent that is necessary to fully constrain its character and behavior. Current data strongly suggest that as for the Earth's PBL, classical Monin-Obukhov similarity theory applies reasonably well to the Martian PBL under most conditions, though with some intriguing differences relating to the lower atmospheric density at the Martian surface and the likely greater role of direct radiative heating of the atmosphere within the PBL itself. Most of the modeling techniques used for the PBL on Earth are also being applied to the Martian PBL, including novel uses of very high resolution large eddy simulation methods. We conclude with those aspects of the PBL that require new measurements in order to constrain models and discuss the extent to which anticipated missions to Mars in the near future will fulfill these requirements. Copyright 2011 by the American Geophysical Union.